Efectos inhibidores de crecimiento del coquito (Cyperus rotundus L.) entre sorgo y soya - Lucena Ugaz, Juan Manuel; Doll, Jerry D. (1976)
Six experiments with sorghum, soybean, and the weed purple nutsedge were conducted in the screenhouse of the Centro Internacional de Agricultura Tropical (CIAT), Palmira, Colombia. The objective was to determine if purple nutsedge produced inhibitors which affect crop growth and to study the effect of competition for mineral elements (N, P and K) between purple nutsedge and crops. It was shown that the purple nutsedge produces growth inhibitors and they are found in greater quantity in the underground portion of the plant. The inhibitors do not persist long in soil. Under the conditions of the experiments, the inhibitors did not affect seed germination but did affect the growth processes of the crops. Purple nutsedge can release inhibitors to soil but these do not have high activity. The inhibitors affect crop species with small seeds more than those with large seeds. Microorganisms in the soil seem not to have much influence on the action of the inhibitors. The competition with purple nutsedge significatly affected the height and weight of sorghum and soybean, and hence, the total amount of N, P and K absorbed by the crops. However, the percentage of N, P and in sorghum and soybean was not altered.